Faktor-Faktor yang Berhubungan dengan Kecemasan pada Petani: Tinjauan Review - Nabylly Aghna Bachtiar; Fitria Saftarina; Ratri Mauluti Larasati; Suryadi Islami (Universitas Malahayati Lampung, 2025)
ABSTRACT Anxiety is an unpleasant feeling of worry or fear accompanied by certain physical symptoms. The prevalence of anxiety has been increasing globally in the last three decades. Farmers are generally faced with a number of working conditions that are considered unfavorable, such as long working hours, monotonous tasks, and dangerous physical work environments. Therefore, farmers are at high risk of experiencing mental health problems that are rarely discussed in scientific publications, especially specifically anxiety. To conclude the factors associated with anxiety in farmers. The literature review method was used in the preparation to conclude the factors that trigger anxiety in farmers, where the literature was obtained from the PubMed, ScienceDirect, DOAJ, Cochrane, and Garuda databases, which are available online. It was found that anxiety in farmers is related to various aspects, both those originating from the work environment such as pesticide use, climate change, land ownership, and isolated work environments as well as those originating from individual factors such as gender, financial condition, and interpersonal relationships. Anxiety in farmers is influenced by individual, occupational, and environmental factors. Factors such as gender, social support, financial condition, pesticide use, land ownership, climate change, and the impact of the COVID-19 pandemic contribute significantly. Understanding and addressing these factors is important to support farmers' mental well-being. Keywords: Farmers, Anxiety, Mental Health ABSTRAK Kecemasan adalah perasaan khawatir atau takut yang tidak menyenangkan yang disertai dengan gejala-gejala tubuh tertentu. Prevalensi kecemasan secara global terus meningkat dalam tiga dekade terakhir. Petani umumnya dihadapkan pada sejumlah kondisi kerja yang dianggap tidak menguntungkan, seperti jam kerja yang panjang, tugas yang monoton, dan lingkungan kerja fisik yang berbahaya. Oleh karena itu petani berisiko tinggi mengalami masalah kesehatan mental yang jarang sekali dibahas dalam publikasi ilmiah terutama secara spesifik pada kecemasan. Tujuanuntuk menyimpulkan faktor-faktor yang berhubungan dengan kecemasan pada petani. Metode tinjauan literatur digunakan dalam penyusunan untuk menyimpulkan faktor yang memicu kecemasan pada petani, dimana literatur diperoleh dari database PubMed, ScienceDirect, DOAJ, Cochrane, dan Garuda yang tersedia secara online. Didapatkan bahwa kecemasan pada petani berhubungan dengan berbagai aspek, baik yang berasal dari lingkungan pekerjaan seperti penggunaan pestisida, perubahan iklim, kepemilikan lahan, dan lingkungan kerja terisolasi maupun yang berasal dari faktor individu seperti jenis kelamin, kondisi finansial dan hubungan interpersonal. Kecemasan pada petani dipengaruhi oleh faktor individu, pekerjaan, dan lingkungan. Faktor seperti jenis kelamin, dukungan sosial, kondisi finansial, penggunaan pestisida, kepemilikan lahan, perubahan iklim, dan dampak pandemi COVID-19 berkontribusi signifikan. Pemahaman dan penanganan faktor-faktor ini penting untuk mendukung kesejahteraan mental petani. Kata Kunci: Petani, Kecemasan, Kesehatan Mental